Wajah Baru Ronggeng Kedempling di Kabupaten Majalengka (Suatu Kajian Historis Tahun 2000-2018) - Aldi Quraysshyhaq; Ayi Budi Santosa (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2021)
The dynamics that occurred in Ronggeng Kedempling dance art in Majalengka Regency during the period 2011-2018, there was an effort to revitalize this art that was initially vacuum and unknown to the public became one of the icons of traditional art originating from Majalengka Regency. The artists made changes to the traditional arts due to negative views and aimed to make Ronggeng Kedempling dance acceptable to the community. The method used in this study is a historical method consisting of heuristics, source criticism, and historiography and assisted by interdisciplinary science, namely sociology and anthropology. While data collection techniques are carried out through literature studies, documentation studies and interviews. Based on the findings, Ronggeng Kedempling dance art is a traditional art undergoing changes and adjustments due to social changes in the supporting community. The change in the supporting component of the arts is the result of creativity and innovation from artists. Various preservation efforts have been made so that this art can withstand the changing conditions of the times. As for the preservation efforts of the artists by doing devolution, ronggeng kedempling dance learning in workshops and in schools and activities in the making of muri records.